Estudio de prefactibilidad para la instalación de una planta generadora de electricidad de 120 MW por medio de concentradores solares cilíndricos parabólicos - Gómez de la Torre Gastello, Alberto (2019)
Propose a viable project of electric generation with solar cylindrical parabolic concentrators. The government is promoting the development of Renewable Energy Resources (RER) by favorable legislation. It is looking to give clean energies, more importance in the energetic matrix. Since the year 2010, the Supervisor Entity for Investment in Energy and Mining (OSINERGMIN) is organizing public auctions to give a 20-year contract for renewable energies only. This assures a market and a demand for a long-term project. Economically the project is not feasible, but financially it is. This is because of the high return demanded for the invested capital. A sensibility analysis was made, where it is established the conditions to make it economically possible, in scenarios similar to the solar photovoltaic sector. The project is based in the use of an alternative CSP (Concentrated Solar Power) technology, which uses the concentrated heat of the sun to generate steam and whirl a turbine, and to deposit some of this heat in a thermal storage, as a means to generate more electricity for more hours and in a consistent way. The south region of Perú, specially Arequipa, has the best conditions for the project, this is because of its worldwide highest radiation level. This project, will inject clean energy to the energetic matrix, avoiding the release of 120 768 tons of C02 to the atmosphere and could supply electricity for a year, to more than 49 617 homes in the country. The specific demand of the project and the selling price is defined by the biannual contract, during the RER auction of the OSINERGMIN. It is signed a contract for 20 years, which gives priority of payment when in conflict with other electric generator agents. This project is proposed using an energetic annual demand of 408 000 MWh, at a subsidized price of 49 USD/MWh. Furthermore, there is an income for Certificates of Emission Reduction (CERS) of 33 042 USD per year. It is calculated for the life of the project a total income of 447 991 024.47 USD. The total investment for the implementation of the power plant is of 301 601 184.07 USD.